PENGARUH KEMAMPUAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KOTA SEMARANG - Dita Aprilia Majid; Susi Sulandari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
The paradigm of the regional development plan has begun in 2011. As the implementation of UU No. No. 22/1999 and UU No. 25/1999, regional development plan is giving to regional government. The regional development plan institution (BAPPEDA) in Semarang City is the institution that work for manage the development plan. Based on Semarang City rule number 13, year 2008, BAPPEDA has duty for implement the regional policy formulation and implementation especially for regional development plan. The purpose of this research is to identity and analyzes performance, skills, and motivation of BAPPEDA Semarang employees. This research is using explanatory quantitative design with the respondent from BAPPEDA employees. The process begin with determine the number of sample from the total BAPPEDA employees. It’s using questionnaire so the answer can be gotten from every variable. The research result of the effects of the ability and motivation to employee performance BAPPEDA Semarang with Kendal Tau formula has correlation between the ability and motivation of the employee's performance. Based on the results of correlation Kendal Tau, significance relationship exists between the ability and motivation of the employee's performance. The need for improvements to improve employee performance.